ANALISIS USABILITY SITUS WEB VOCABULARY CONTROL NUSANTARA MENGGUNAKAN METODE WEBUSE - Danar Shidky Pertiwi; Danang Dwijo Kangko; Indah Kurnianingsih (Perpustakaan Nasional RI, 2021)
Vocabulary Control Nusantara Website is a voluntary movement that focused work on developing the index language automation system web-based, which is everyone can contribute to the development of site content. From the beginning of the movement until now Vocabulary Control Nusantara Website still in the development stage and no assessment evaluates the level of usability of the website. Therefore, usability analysis is needed to measure the level usability of the Vocabulary Control Nusantara Website and also to predict the potential benefits which will be obtained later when this movement complete. This study does a usability analysis on the homepage and backend page of the Vocabulary Control Nusantara Website by using the WEBUSE method to measure how good the level usability website. The analysis results show on the homepage page get the level usability “Good”, although there are two categories on the backend page which gets the level usability “Moderate”. Besides, there are some unsolved problems that are recommended to further testing and implementation redesign websites.